Considering future qualification for regulatory science in the early development of microphysiological systems: a case study of microthrombosis in a Vessel-on-Chip - Weener, Huub J.; Middelkamp, Heleen H. T.; Van der Meer, Andries D. (Frontiers in Toxicology, 2024)
Microphysiological systems (MPS) and Organs-on-Chips (OoCs) hold significant potential for replicating complex human biological processes in vitro. However, their widespread adoption by industry and regulatory bodies depends on effective qualification to demonstrate that these models are fit for purpose. Many models developed in academia are not initially designed with qualification in mind, which limits their future implementation in end-user settings. Here, we explore to which extent aspects of qualification can already be performed during early development stages of MPS and OoCs. Through a case study of our blood-perfused Vessel-on-Chip model, we emphasize key elements such as defining a clear context-of-use, establishing relevant readouts, ensuring model robustness, and addressing inherent limitations. By considering qualification early in development, researchers can streamline the progression of MPS and OoCs, facilitating their adoption in biomedical, pharmaceutical, and toxicological research. In addition, all in vitro methods must be independent of animal-derived materials to be considered fully fit for purpose. Ultimately, early qualification efforts can enhance the availability, reliability, and regulatory as well as ethical acceptance of these emerging New Approach Methodologies.